Intersection of atrial fibrillation and heart failure with mildly reduced and preserved ejection fraction in >400 000 participants in the Get With The Guidelines‐Heart Failure Registry. (20th November 2022) - Patel, Ravi B.; Greene, Stephen J.; Xu, Haolin; Alhanti, Brooke; Peterson, Pamela; Yancy, Clyde W.; Piccini, Jonathan; Fonarow, Gregg C.; Vaduganathan, Muthiah
Abstract: Aims: Although atrial fibrillation (AF) frequently coexists with heart failure with preserved ejection fraction (HFpEF), few data are available evaluating AF‐specific care patterns and post‐discharge outcomes in patients hospitalized for HFpEF. We evaluated AF‐specific medical therapies and post‐discharge outcomes among patients hospitalized for heart failure with mildly reduced ejection fraction (HFmrEF) or HFpEF by AF history. Methods and results: Trends in AF prevalence were evaluated among patients hospitalized for HFmrEF or HFpEF in the Get With The Guidelines‐Heart Failure Registry from 2014 to 2020. Among those with linked Centers for Medicare & Medicaid Services post‐discharge data, we assessed associations of AF with 12‐month outcomes and determined trends in post‐discharge prescriptions. Among 429 464 patients (median age 76 years [interquartile range 65–85], 57% women), 216 486 (50%) had a history of AF. Over time, the proportion of patients with AF increased slightly. Among the 79 895 patients with post‐discharge data, AF was independently associated with higher risk of mortality and all‐cause readmissions at 12 months, with stronger associations in HFpEF than in HFmrEF (mortality hazard ratio [HR] 1.13, 95% confidence interval [CI] 1.09–1.16 vs. HR 1.03, 95% CI 0.97–1.10; p interaction = 0.009). Anti‐arrhythmic drug use after heart failure hospitalization was low (18%) and increased modestly over time. Amiodarone accounted for 71% of total anti‐arrhythmic drug prescriptions. Overall use of anticoagulants after heart failure hospitalization has significantly increased from 52% in 2014 to 61% in 2019, but remained modest. Conclusion: Prevalence of AF is rising among patients hospitalized with HFpEF. Those with comorbid AF face elevated post‐discharge risks of death and rehospitalization. Current use of pharmacological rhythm control is low. Abstract : Atrial fibrillation in heart failure with mildly reduced and preserved ejection fraction. AF, atrial fibrillation; CI, confidence interval; GWTG‐HF, Get With The Guidelines‐Heart Failure; HF, heart failure; HFmrEF, heart failure with mildly reduced ejection fraction; HFpEF, heart failure with preserved ejection fraction; HR, hazard ratio.